Efficacy of Different Laboratory Tests to Diagnose Helicobacter pylori Infection - Islam, MM Shahin Ul; Nahar, Shamsun; Sarker, Mst Naznin; Salimullah, ASM; Rahman, Mohammad Asadur; Ahmed, Dewan Saifuddin; Hasan, Mohammad Quamrul; Raihan, ASMA; Bhuiyan, Mujibur Rahman; Sarker, Shafiqul Alam; et al. (Faridpur Medical College Journal, 2013)
Helicobacter pylori is a Gram negative bacteria which causes chronic gastritis, peptic ulcer disease, primary B-cell gastric lymphoma, and adenocarcinoma of the stomach. There are a set of laboratory tests to diagnose H. pylori infection with a variable accuracy, they are divided into non-invasive tests and invasive tests. Non-invasive tests include serology, urea breath test (UBT) and stool antigen test (SAT). Invasive tests include rapid urease test (RUT), histology and culture. This cross sectional study was carried out in the Department of Gastroenterology, Bangabandhu Sheikh Mujib Medical University (BSMMU) and H. pylori laboratory of International Centre for Diarrhoeal Disease Research, Bangladesh (ICDDR,B) from July 2008 to September 2009 to evaluate the efficacy of RUT, SAT and Culture as a diagnostic tool for H. pylori. Dyspeptic patients were collected from outpatient department of BSMMU. Out of 224 dyspeptic patients 149 patients had ulcers or erosions in the stomach or duodenum. Stool sample could be collected from 139 patients. RUT has sensitivity of 100%, specificity 80.28%, positive predictive value 85% and negative predictive value 100%. Regarding culture, sensitivity is 100%, specificity 94.37%, positive predictive value 95% and negative predictive value 100%. Stool antigen test has sensitivity 95.94%, specificity 92.31%,positive predictive value 93% and negative predictive value 95%. DOI: http://dx.doi.org/10.3329/fmcj.v8i1.16890 Faridpur Med. Coll. J. 2013;8(1): 11-14